Fear of coronavirus and health literacy levels of older adults during the COVID-19 pandemic - Ayaz-Alkaya, Sultan; Dülger, Hanifi; Dülger, Hanifi (Mosby-Elsevier, 2022)
This study aimed to examine the fear of coronavirus and the health literacy levels of older adults during the pandemic. The sample consisted of 304 older adults from five family health centers in Turkey between April and May 2021. The data were collected using the Fear of COVID-19 Scale and the Health Literacy Scale. The fear of COVID-19 was found to be higher in women, those with chronic diseases, and those who found the epidemic measures insufficient (p < 0.05). The health literacy level was found to be higher in those with high education level, those in the 65-74 age group, and those with not using regular medicine (p < 0.001). The health literacy of older adults was a slightly above moderate level and the fear of COVID-19 was at a moderate level. Health literacy levels of older adults may be increased with written, visual, and verbal health trainings. (c) 2021 Elsevier Inc. All rights reserved.
Keywords: Covid-19; Fear; Health Literacy; Pandemic; Older Adult